Mergers in Sharia Banking and Their Impact on Employee Performance: The Role of Self-Efficacy and Affective Commitment as Moderating - Dewi Agustiyana; Rozikan; Adin Gustina (Journal of Islamic Economic and Business Research, 2023)
Human resources are one of the main aspects of an organization. Having quality resources can affect the success of an organization. Therefore, companies need to improve employee performance, one of which is by making organizational changes. This study aims to determine the effect of organizational change on employee performance moderated by self-efficacy and affective commitment. This research applied a qualitative method, and the questionnaire data involved 155 respondents from an unlimited total population. The analysis used in this study is the Structural Equation Modelling (SEM) method based on variance, namely Partial Least Square (PLS). The results of the study showed a significant effect between organizational change and employee performance. The affective commitment variable was also able to moderate the effect of organizational change on employee performance, while self-efficacy was not able to moderate the effect of organizational change on employee performance.